Molecular variants of Grapevine rupestris stem pitting-associated virus infecting grapevines (Vitis spp.) in Brazil - Fajardo,Thor Vinícius Martins (2017)
ABSTRACT: Grapevine rupestris stem pitting-associated virus (GRSPaV) is one of the most common viruses of grapevine. It is involved in the graft-transmissible disease rupestris stem pitting of the rugose wood complex. The objective of the research was to perform the molecular characterization of the coat protein (CP) gene of sixteen Brazilian GRSPaV isolates aiming to determine the occurrence of molecular variants (strains) of this virus. Nine grapevine samples were evaluated, from which dsRNA was extracted. Nucleotide sequences were generated by Next generation sequencing (NGS). Fifteen complete sequences of the GRSPaV CP gene were obtained and phylogenetically analyzed. Multiple alignments of the sequences showed identities of nucleotides ranging from 82% to 99%, suggesting high variability among the CPs of Brazilian isolates. The study revealed that genetic variability of GRSPaV comprising three molecular variants is also present in Brazilian grapevine genotypes.